Effects of long-term diet supplementation with Gliricidia sepium foliage mixed with Enterolobium cyclocarpum pods on enteric methane, apparent digestibility, and rumen microbial population in crossbred heifers. (19th February 2019) - Molina-Botero, Isabel Cristina; Montoya-Flores, Maria Denisse; Zavala-Escalante, Lucas M; Barahona-Rosales, Rolando; Arango, Jacobo; Ku-Vera, Juan Carlos
Abstract: In the last decades, strategies have been evaluated to reduce rumen methane (CH 4 ) production by supplementing tropical forages rich in secondary compounds; however, most of these beneficial effects need to be validated in terms of their persistence over time. The aim of this study was to assess CH4 emissions over time in heifers fed with and without Gliricidia sepium foliage (G) mixed with ground pods of Enterolobium cyclocarpum (E) . Two groups of 4 crossbred ( Bos taurus x Bos indicus ) heifers (284 ±17 kg initial weight) were fed with 2 diets (0% and 15% of a mixture of the pods and foliage [E + G:0 and E + G:15, respectively]) over 80 d, plus 2 wk before the experiment, in which every animal was fed a legume and pod-free diet. Every 14 d, CH4 production, apparent digestibility, volatile fatty acids (VFA), and microbial population were quantified for each animal. The experiment was conducted with a repeated measurements design over time. Diets fed differed in terms of their crude protein (CP), condensed tannins, and saponins content supplied by E. cyclocarpum and G. sepium . For most of the experiment, dry matter intake (DMI) and digestible dry-matter intake (DDMI ) were 6.3 kg DMI/d and 512 g DDMI/kg, respectively, for both diets (diet: P > 0.05 ). Apparent digestible crude protein (DCP ) was reduced by 21 g DCP/kg DM when the diet was supplemented with E + G:15 ( P = 0. 040 ). Molar proportions of VFA's in the rumen did not differ between diets or in time ( P > 0.05 ). Daily methane production, expressed in relation to DMI, was 23.95 vs. 23.32 g CH4 /kg DMI for the diet E + G:0 and E + G:15, respectively (diet: P = 0.016 ; Time: P > 0.05 ). Percent gross energy loss as CH4 ( Ym ) with grass-only diets was above 8.1%, whereas when feeding heifers with the alternate supplementation, Ym values of 7.59% ( P = 0.016 ) were observed. The relative abundance of total bacterial, protozoa, and methanogenic archaeal replicates was not affected by time nor by the incorporation of legume and pods into the diet ( P > 0.05 ). Results suggest that addition of G. sepium mixed with E. cyclocarpum pods can reduce CH4 production in heifers and this response remains over time, without effect on microbial population and VFA concentration and a slight reduction in CPD digestibility.